Safer and Faster Humanitarian Demining with Robots - Keçeci, Emin Faruk (IGI Global, 2012)
The need to clean almost 1 million landmines on the Turkish border poses a great challenge to the Turkish military, both as a safety and a feasibility issue. In order to achieve this task, an Explosive Ordnance Disposal (EOD) robot has been designed and a prototype has been manufactured. The robot has the capability of working in task space. The uniqueness of this research is that the design criteria and the prototype procedure is explained in detail. After the testing of the prototype, the research results are concluded—which functions the future EOD robots should have and how these functions can improve the performance and ease of use of this type of military robots. Autonomy, use of an advisory system, and automatic camera manipulation can improve the future EOD robots dramatically.
Keywords: Wireless Home Automation Systems; Artificial intelligence; Safer; Human–computer interaction; Robot; Aeronautics; Computer science; Systems engineering; Task (project management); Engineering; Computer security; Physical Sciences; FOS: Electrical engineering, electronic engineering, information engineering; Electrical and Electronic Engineering; Simulation